2009
DOI: 10.1039/b820768b
|View full text |Cite
|
Sign up to set email alerts
|

Direct and short-time uptake of [70]fullerene into the cell membrane using an exchange reaction from a [70]fullerene–γ-cyclodextrin complex and the resulting photodynamic activity

Abstract: [70]Fullerene (C70) was directly incorporated into the cell membrane using an exchange reaction from a C70-gamma-cyclodextrin (gamma-CDx) complex within 10 min and the incorporated C70 acted as a photodynamic sensitiser for a cancer cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 16 publications
1
37
0
1
Order By: Relevance
“…To the best of our knowledge, aside from a few relevant investigations [25,47,48], plasma membrane-targeted PDT remains largely unexplored.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…To the best of our knowledge, aside from a few relevant investigations [25,47,48], plasma membrane-targeted PDT remains largely unexplored.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…1,2 Due to the formation of a long-lived triplet state and the high photoproduction ability of ROS, fullerenes have attracted significant attention as PS of PDT. [3][4][5][6][7][8][9][10][11][12][13] We have previously reported that liposomal lipid membrane can be used for solubilization of unmodified [60]fullerenes (C 60 ) to overcome their poor water solubility. The produced cationic lipid membrane incorporating C 60 (LMIC 60 ) showed high cytotoxicity under light irradiation between 350-500 nm.…”
mentioning
confidence: 99%
“…We have already reported the incorporation of C 70 into a cell membrane, with the material successfully acting as a photodynamic sensitizer for a cancer cell. 28 The experiments, however, were carried out in physiological saline (0.9 w/v% NaCl solution). Given that the C 70 ·γ-CDx complex was much more labile than the other fullerene·γ-CDx complexes, it was envisaged that the C 70 ·γ-CDx complex could decompose and release C 70 , which could interfere with the level of uptake in the HeLa cells via its incorporation into several proteins, low density lipoprotein (LDL) and high density lipoprotein (HDL), in the fetal calf serum.…”
mentioning
confidence: 99%